2016
DOI: 10.23887/janapati.v5i3.9922
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Pembelajaran Berbasis Web Untuk Matakuliah Kurikulum dan Pengajaran di Jurusan Pendidikan Teknik Informatika Universitas Pendidikan Ganesha

Abstract: Perkembangan teknologi informasi dan komunikasi kini telah mengubah cara pandang dan bertindak masyarakat dalam menghabiskan waktu untuk bekerja dan mengatasi segala permasalahannya. Bentuk-bentuk perkembangan dan perubahan teknologi informasi pada dasarnya merubah aktifitas masyarakat dalam dunia nyata ke dalam aktifitas dunia maya. Banyak lagi bentuk perubahan lainnya terjadi dalam sendi-sendi kehidupan masyarakat yang dibawa oleh perkembangan dan kemajuan TI, tidak terkecuali, dalam dunia pendidikan. Dampak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
27

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 0 publications
1
23
0
27
Order By: Relevance
“…Although the presence of technology does not guarantee equality and accessibility in learning, it can increase students' knowledge in various fields. Forms of development and changes in information technology can change the habits of community activities, no exception in the world of education (Divayana et al, 2016). With the development of the internet, and the availability of video capture devices such as digital cameras, cellphones with cameras, digital video collection sizes are fast on the internet (Li et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Although the presence of technology does not guarantee equality and accessibility in learning, it can increase students' knowledge in various fields. Forms of development and changes in information technology can change the habits of community activities, no exception in the world of education (Divayana et al, 2016). With the development of the internet, and the availability of video capture devices such as digital cameras, cellphones with cameras, digital video collection sizes are fast on the internet (Li et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Some empirical literature indicates that the integration of technology in learning provides great opportunities for the effectiveness and success of the learning process. For example, learning can be increased its effectiveness through the use of e-learning with the Chamilo platform [27], with the use of mobile learning [28], [29], Moodle [30], web-based platform [31], [32], and Learning Management System [33]. In addition, Astuti [34] and Putri [35] research on the development of web-based learning media also indicated an increase in adversity quotient from students and potential efficiency for lecturers in preparing teaching materials for lectures in class.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this mission, one of them is pursued by a quality learning process in accordance with the development of science and technology, one of which is the learning process through web-based learning media. The web is a system that provides all information, including text, images, animation, sound, and / or a combination of these, both static and dynamic (Rahayu et al, 2019;Qondias et al, 2016;Divayana et al ., 2016;Nugroho, 2012). The rapid development of technology has made many universities support the use of technology in learning, especially the internet.…”
Section: Introductionmentioning
confidence: 99%